Technical Characteristics of Curriculum-Based Measurement With Students Who Are Deaf. (11th May 2020) - Lam, Elizabeth A; Rose, Susan; McMaster, Kristen L
Abstract: This study compared the reliability and validity of student scores from paper–pencil and e-based assessments using the "maze" and "silent reading fluency" (SRF) tasks. Forty students who were deaf and hard of hearing and reading between the second and fifth grade reading levels and their teachers ( n = 21) participated. For maze, alternate form reliability coefficients obtained from correct scores and correct scores adjusted for guessing ranged from r = .61 to .84 ( p s < .01); criterion-related validity coefficients ranged from r = .33 to .67 (most p s < .01). For SRF, reliability coefficients obtained from correct scores ranged from r = .50 to .75 ( p s < .01); validity ranged from r = .25 to .72. Differences between student performance on paper–pencil and e-based conditions were generally non-significant for maze; significant differences between conditions for SRF favored the paper–pencil condition. Findings suggest that maze holds promise, with inconclusive results for SRF.